Thai Consumer Decision-making Styles on Imported Cosmetic Brand Products - Chaisitthiroj, Nussara (2007)
Consumer decision-making has long been an interesting issue for both academics and practitioners. It is believed that each consumer interacts with a market with particular decision-making styles and these styles are stable overtime. This dissertation aimed to investigate Thai female consumer decision-making styles on imported cosmetic products and to segment them based on those styles. To achieve the objectives, Sproles and Kendall's (1986) Consumer Style Inventory (CSI) was employed. From a sample of 225 Thai females who buy foreign brand cosmetics, a new eight-factor model of CSI explaining these female consumers' decision-making styles was emerged using a factor analysis. Then, eight segments of consumers were identified using a cluster analysis. The results indicate that cluster 1 could represent most Thai female consumers who purchase imported cosmetics since the majority of the respondents belong to this cluster.